INHIBITION OF PYROPHOSPHATE - FRUCTOSE-6-PHOSPHATE 1-PHOSPHOTRANSFERASE BY IMIDODIPHOSPHATE - Rowntree, E; Kruger, N (1992)
The aim of this work was to examine the effect of imidodiphosphate on the kinetic properties of pyrophosphate:fructose 6-phosphate 1-phosphotransferase. The enzyme was purified about 700-fold from mature tubers of Solanum tuberosum cv. Maris Piper. Imidodiphosphate was not metabolised by this enzyme. The apparent ability of imidodiphosphate to act as a phosphoryl donor was due to contamination of this compound by inorganic pyrophosphate. When enzyme activity was measured in the glycolytic direction, imidodiphosphate per se was a mixed inhibitor with respect to both fructose 6-phosphate and inorganic pyrophosphate. Comparison of the kinetic constants with the estimated concentration of reactants in vivo indicates that enzyme activity could be substantially inhibited in spinach leaves fed with imidodiphosphate (H.E. Neuhaus and M. Stitt, Plant Sci.m 76 (1991) 49-55). © 1992.